Mandate for Women on Boards: Is it Enough? - Sethi, Sanchli (Frontiers in Law, 2023)
The Companies Act, 2013, mandates the appointment of at least one woman on the board of directors of a company. While it does not mention whether she should be an independent director or not, the legislation creates a reservation based on sex. The paper examines whether and why such a mandate is needed for companies to be gender diverse. It highlights certain problems with the current legislation and provide rectifying measures for the same.